Efforts to Improve Arabic Speaking Skills Through Muhadhoroh Activities at the Al Ukhuwah Sukoharjo Islamic Boarding School - Farid Fadilah; Nurul Latifatul Innayati (al-Afkar, Journal For Islamic Studies, 2024)
This research is motivated by the phenomenon of the low quality of students in learning the Arabic language. The muhadhoroh activity is offered as a solution in an effort to improve Arabic speaking skills. This activity aims to deepen religious understanding and enhance Arabic speaking skills through discussions or exchanges of ideas among participants. In Arabic language learning, speaking skills involve the ability to express ideas, opinions, or feelings of the speaker through words understandable to the interlocutor. The research design used is a type of field study with a qualitative descriptive approach. The research approach employed is phenomenological. The purpose of this study is to understand the steps of the muhadhoroh activity at Al-Ukhuwah Sukoharjo Islamic boarding school and the benefits that students can gain from muhadhoroh activities related to Arabic speaking skills. Muhadhoroh is a learning activity aimed at improving public speaking skills in Arabic and boosting the confidence of the students.